Teachers for Rural Schools : Experiences in Lesotho, Malawi, Mozambique, Tanzania, and Uganda - Mulkeen, Aidan; Chen, Dandan (Washington, DC: World Bank, 2012)
Achieving universal primary education and "Education for All" (EFA) is one of the development priorities within the context of the millennium development goals. In many Sub-Saharan African countries, one of the key challenges is to provide good-quality basic education to the 10-20 percent of primary school-age children who are still out of school. Among these out-of-school children, the most difficult to reach are living in rural and remote areas. In recent years, large investments have greatly improved school infrastructure and access, but finding effective ways of supplying teachers to schools in rural and remote areas remains a key policy concern. To examine the issues related to providing teachers for rural schools, five countries-Lesotho, Malawi, Mozambique, Tanzania, and Uganda-prepared national case studies and, along with representatives from Zambia, came together for a workshop on "policy, planning, and management of rural primary school teachers" in Lesotho in May 2005. Building on the national reports, this workshop considered the challenges of teacher provision in rural areas and examined the viable policy options.